Asupan zat gizi mikro dengan fungsi kognitif pada lanjut usia - Ade Rahmawati; I Dewa Putu Pramantara; Martalena Purba (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2012)
Background: The elderly population in Indonesia increased signifi cantly in the last two decades as the life expectancy increase from 66.7 years to 70.5 years with impact to the emergence of diseases in the elderly. One of them is degradation of cognitive function that may disrupt productivity, daily activities, and quality of life of the elderly. Adequate micronutrients intake may help in maintaining cognitive function.Objectives: To identify association between intake of micronutrients (vitamin B6, folate, vitamin C, and vitamin E) and cognitive function of the elderly at Among Yuswa Club of Banteng Baru, District of Sleman.Methods: This was an observational study with cross sectional design. Subjects were elderly people at Among Yuswa Club of Banteng Baru, District of Sleman. Data on cognitive function was obtained using the Mini Mental State Examination (MMSE) and intake of micronutrients were collected using Semi Qualitative Food Frequency Questionnaire (SQFFQ). The data was analysed by chi square and logistic regression tests.Results: The result showed statistically signifi cant association between cognitive function and intake of vitamin B6 (p=0.010; RP=2.514; 95%CI=1.133-5.575), vitamin C intake (p=0.011; RP=3.039; 95%CI=1.454-6.353) and vitamin E intake (p=0.021; RP=1.266; 95%CI=1.057-1.516); meanwhile folate intake has no signifi cant association with cognitive function (p>0.05).Conclusion: There were signifi cant associations between intake of vitamin B6, vitamin C and vitamin E with cognitive function. There was no signifi cant association found between intake of folate and cognitive function in the elderly.